실시간 온라인 교육 플랫폼의 학습만족도와 지속사용의도에 영향을 미치는 요인에 관한 연구 - 매사양(Si-Yang Mei); 이동명(Dong-Myung Lee) (한국콘텐츠학회 논문지, 22(6), 2022)
This study aims to help revitalize the real-time online education platform market by analyzing the instructor characteristics, content characteristics, and platform characteristics of real-time online education platforms for local learners in China. A total of 670 questionnaires were collected through an online survey and an empirical analysis was conducted. As a result of the analysis, first, except for attractiveness, which is the characteristic of the instructor, professionalism and sincerity had a significant positive influence on both learning satisfaction. Second, the usefulness, abundance, and appropriateness of content characteristics had a significant positive influence on learning satisfaction. Third, except for interaction, which is a platform characteristic, technology and convenience confirmed a significant positive influence relationship on both learning satisfaction. Fourth, learning satisfaction had a significant positive effect on the intention to continue using. This study presented practical implications for real-time online education platform and future research directions. 본 연구는 중국 현지의 학습자들을 대상으로 실시간 온라인 교육 플랫폼의 교수자 특성, 콘텐츠 특성과 플랫폼특성이 학습만족도 및 지속사용의도에 미치는 영향을 분석함으로써 실시간 온라인 교육 플랫폼 시장의 활성화에 도움이 되고자 한다. 설문조사를 통해 총 670부 설문지를 수집하여 실증분석을 실시하였다. 분석 결과, 첫째, 교수자의 특성인 매력성을 제외하고 전문성과 성실성은 학습만족도에 모두 유의미한 정의 영향관계가 있었다. 둘째, 콘텐츠 특성의 유용성, 풍부성과 적절성은 학습만족도에 모두 유의미한 정의 영향 관계가 있었다. 셋째, 플랫폼 특성인 상호작용성을 제외하고, 기술성과 편리성은 학습만족도에 모두 유의미한 정의 영향 관계를 확인하였다. 넷째, 학습만족도는 지속사용의도에 유의한 긍정적인 영향을 미쳤다. 따라서 실시간 온라인 교육 플랫폼 시장의 활성화를 위해 교수자 특성, 콘텐츠 특성과 플랫폼특성에 대하여 실제로 느끼는 효용의 가치를 높였다는 점에서 큰 의미가 있다. 본 연구는 실시간 온라인 교육 플랫폼 실무적 시사점과 향후 연구방향을 제시하였다.